What do they want? Millennials and role of libraries in Pakistan - Soroya, Saira Hanif; Ameen, Kanwal (The Journal of Academic Librarianship, 2018)
The present study is aimed at determining the future role of libraries in Pakistan as perceived by the Millennials (people born during the 1980's and late 1990's) considering the current ongoing digital development. The quantitative research design, based on survey has been used for the study. The population consisted of students from large and medium sized general universities of Lahore, Pakistan. Stratified purposive sampling technique was carried out to select the pool of the subjects e. A self-constructed and validated instrument was used to collect data. The collected data was analyzed using SPSS (16.0). The results revealed that Millennials want future libraries to allow easy access to a wide range of reading material in both print and digital form. They want to be able to round the clock access to electronic and print resources.
Keywords: 21st century library users; Future role of libraries; Millennials; Pakistan; dept.ils

Application of marketing approach in academic libraries: an exploratory study of Punjab University Libraries (PULs) - Soroya, Saira Hanif; Ameen, Kanwal (Pakistan Library & Information Science Journal, 2017)
Keywords: dept.ils

Reading Trends of Youth in Pakistan: A Pilot Study - Soroya, Saira Hanif; Ameen, Kanwal (Pakistan Journal of Information Management and Libraries, 2016)
The present study, a part of researcher's Ph.D. project, aimed at exploring the reading trends of young Pakistani students (i.e., Generation Y: born during the 1980s and early 1990s, also known as internet generation), and the impact of digital media on their reading behavior. It was conducted as a pilot study on final year's master level students of the University of the Punjab. Quantitative research design, based on a survey was used. Convenient sampling technique was used to collect data from 50 students through questionnaire survey. It revealed that the students' reading behavior has been significantly changed during the last five years. Their overall reading time and digital reading time has been increased due to the availability of digital devices and digital reading material. The findings of this study are helpful in identifying the trends of reading behavior as well as in planning and designing library services with regard to the considering of the behavior of the students.
Keywords: dept.ils